THE DISTINCTIVE MENTAL FEATURES OF OUR ENTREPRENEURIAL CULTURE (Scientific journal of the Fergana State University, 2023)
This article analyzes the concept of entrepreneurial culture, its content and essence, the formation and improvement of its specific features from a scientific and theoretical point of view. When forming the socio-economic, cultural and legal foundations of entrepreneurial culture, an attempt was made to analyze the significance of our national traditions and customs, as well as the relationship of universal values and national heritage from a socio-cultural point of view.